Investigação genômica em pacientes com deficiência intelectual ou atraso global do desenvolvimento assistidos na rede pública de saúde do estado de Goiás - D’Ávila, Ana Julia da Cunha Leite (2022)
Intellectual Disability (ID) is a complex and heterogeneous clinical condition that affects about 1 to 3% of children and adolescents worldwide, and that can be caused by a variety of environmental and/or genetic factors. There are a variety of human genetic variants already identified for ID, from small variants to larger structural variants that affect thousands to millions of nucleotides. GTG banding karyotyping and microarray chromosome analysis (CMA) are often used to identify the genetic causes of ID, especially in cases Where the clinical evaluation indicates the syndromic form of ID. The use of next generation sequencing technologies for the diagnosis of ID has made it possible to expand the detection of new mutations and new genes associated with ID. The aim of this study was to perform total exome sequencing with gene panel analysis for intellectual disability, in patients who presented karyotype without structural and/or numerical alterations and did not present pathogenic copy number variations (CNVS) in the CMA. A retrospective cohort of 369 patients of both sexes with clinical indications of DI and/or global developmental delay was evaluated in the study. Peripheral blood samples were collected to perform cytogenetic analysis and gene sequencing. GTG banding was performed for all patients following the standard protocol. CMA was performed for patients who did not present structural and/or numerical alterations in the karyotype. Genomic DNA was isolated from patients and their biological parents in order to determine the origin of the CNVs found. Cases that were not diagnosed after performing the karyotype and CMA were referred for exome sequencing with gene panel analysis for intellectual disability, which encompassed 1,252 genes. With the karyotype, it was possible to identify chromosomal alterations in 34.7% (128/369) of the patients. CMA was performed in 83 patients who had results with no alterations in karyotype (46,XX or 46,XY) with a diagnosis rate of 21.7% (18/83). Exome sequencing for target genes was performed in 19 trios of families that had negative results in previous methodologies. Gene panel analysis of exome data identified mutations in 63.1% (12/19) of cases, of which 75% (9/12) were pathogenic variants, 8.3% (1/12) probably pathogenic and in 16.7% (2/2) VUS. Of the total variants identified, 75% (9/12) were de novo mutations and 25% (3/12) had mutations inherited from healthy parents. The most prevalent variants were missense-type mutations (66.7%) followed by nonsense-type mutations 16.7%), frameshift (8.3%) and loss CNV (8.3%). With the three methodologies applied, it was possible to identify the genetic causes of ID in 42.3% (156/369) of the patients. In conclusion, our results show different methodologies that can be used for the genetic diagnosis of ID and that exome sequencing with gene panel analysis provides an efficient diagnostic strategy when combined with clinical and laboratory screening.